99^9/9^99
=(9*11)^9/9^99
=(9^9*11^9)/9^99
=11^9/9^(99-9)
=11^9/9^90
-O hopes.
Hi everybody, I am looking for some help with the following question, it seems more or less easy, but is getting a little challenging for me.
99^9/9^99 (for column A)
11^9/9^90 (for column B)
The answer states that both columns are equal, I've been trying using exponents rules, power rules and some factoring but I can't get it quite right.
If someone could show how to prove that both columns are equal, it will end my lack of sleep
thanks in advance to all